Review article: pathophysiology and management of primary biliary cholangitis. Issue 7 (19th August 2020) - Leung, Kristel K.; Deeb, Maya; Hirschfield, Gideon M.
Summary: Background: Primary biliary cholangitis (PBC), an immune‐mediated disease characterised by destruction of intrahepatic bile ducts, results in progressive damage to the biliary tree, cholestasis and ultimately advanced liver disease. In the last decade, advances in practice have improved clinical care, driven novel therapeutic options and improved risk stratification tools. Aims: To provide an overview of the disease characteristics of PBC and review a patient‐centred management approach for the clinical team caring for those with PBC. Methods: We reviewed the current literature and guidelines on PBC with a focus on management and therapies. Results: A confident diagnosis of PBC is usually made based on serum liver tests and immune serology. Management of PBC should focus on three main 'process' pillars: (a) treat and risk‐stratify through use of biochemical and prognostic criteria; (b) manage concurrent symptoms and other associated diseases; and (c) stage disease, monitor progression and prevent complications. With ongoing complexities in management, including a newly licensed therapy (obeticholic acid) and alternative non‐licensed treatments and ongoing clinical trials, discussion with PBC expert centres is encouraged. Conclusions: PBC is a dynamic disease wherein current treatment goals have become appropriately ambitious. Goals of care should prioritise prevention of end‐stage liver disease and amelioration of patient symptom burden for all.